Preventive systems in secondary education in Accordance with the Applications of the SOBANE Strategy - slimani , sabrina; Mouleme, Manel (Journal of Social Sciences and Humanities, 2023)
Preventive systems in educational institutions depend on the diagnosis of the prevailing conditions of schooling by conducting an assessment of the current situation and comparing the results obtained from the field with the requirements to be provided according to the criteria and physiological data of individuals. This would determine the areas of comfort, distress, and conditions that ensure the safety and security of pupils in their school environment. Since the type of relationship is quantity-quality, the descriptive analytical approach is used to highlight the descriptions of different aspects of the school building such as location, heating, lighting, ventilation, the land area devoted to various activities, Health and security conditions, playgrounds, restaurants, libraries and so on. To achieve the study's aims, the ergonomic Analysis Method of Health and Educational Safety SOBANE is followed to prevent psychological and social hazards. It consists of four techniques (investigation, observation, analysis, and testing). This depends on the participation of all participants in the educational process at all levels, and it seeks to improve the educational quality of life of the pupil.